The confession [Priznanie anglicky] - Grisham, John, 1955- (Arrow Books, 2011)
An innocent man is days from execution. Only a guilty man can save him. Travis Boyette is a murderer. In 1998, in the small East Texas city of Sloan, he abducted, raped, and strangled a popular high-school cheerleader. He buried her body so that it would never be found, then watched and waited as police and prosecutors arrested Donte Drumm.